Peroxide Responsive Regulator PerR of group A Streptococcus Is Required for the Expression of Phage-Associated DNase Sda1 under Oxidative Stress - Wang, Chih-Hung (Public Library of Science, 2013)
The peroxide regulator (PerR) is a ferric uptake repressor-like protein, which is involved in adaptation to oxidative stress and iron homeostasis in group A streptococcus. A perR mutant is attenuated in surviving in human blood, colonization of the pharynx, and resistance to phagocytic clearance, indicating that the PerR regulon affects both host environment adaptation and immune escape. Sda1 is a phage-associated DNase which promotes M1T1 group A streptococcus escaping from phagocytic cells by degrading DNA-based neutrophil extracellular traps. In the present study, we found that the expression of sda1 is up-regulated under oxidative conditions in the wild-type strain but not in the perR mutant. A gel mobility shift assay showed that the recombinant PerR protein binds the sda1 promoter. In addition, mutation of the conserved histidine residue in the metal binding site of PerR abolished sda1 expression under hydrogen peroxide treatment conditions, suggesting that PerR is directly responsible for the sda1 expression under oxidative stress. Our results reveal PerR-dependent sda1 expression under oxidative stress, which may aid innate immune escape of group A streptococcus.